Moulding South African Public Opinion on Economic Cooperation with Russia - GORELIK Boris Moiseevich (Ученые записки Института Африки Российской академии наук)
A study of over 300 articles and opinion pieces in popular and academic publications in South Africa, issued in 2016–2021, shows that South African journalists and political scientists are sceptical of large state-sponsored economic projects involving Russian state companies.